Genetic Diversity and Conservation of Bomarea ovallei (Phil.) Ravenna: Microsatellite Markers Reveal Population Vulnerability in the Atacama Desert - Valeska Rozas-Lazcano; Mariel Mamani-Gómez; Irina Rojas-Jopia; Mariana Arias-Aburto; Roberto Contreras-Díaz (Plants)
The Atacama Desert, the driest and oldest desert on Earth, hosts a unique floral phenomenon known as the Desierto Florido (Flowering Desert), which occurs sporadically in response to rare rainfall events. Bomarea ovallei (Phil.) Ravenna is an endemic and endangered species of the Atacama Desert. However, its populations are geographically restricted and potentially vulnerable to genetic erosion due to isolation and extreme environmental conditions. This study aims to assess the genetic diversity of B. ovallei populations and develop microsatellite markers using next-generation sequencing (NGS) technology. A total of 268 microsatellite loci were identified, and 34 co-dominant markers were successfully developed for the first time in B. ovallei. Genetic diversity analysis using eight fluorescently labeled SSR markers revealed low genetic diversity across four populations, with the highest diversity observed in the QCA population, located within Llanos de Challe National Park, and the lowest in the TOTO population, which is highly exposed to anthropogenic activities. UPGMA and STRUCTURE analyses revealed three genetic clusters and high admixture among populations, suggesting historical or ongoing gene flow despite geographical separation. The presence of non-polymorphic loci and low PIC values in some markers further supports limited genetic variation. The newly developed microsatellite markers offer a valuable tool for future genetic studies, enabling the monitoring of genetic diversity and informing strategies for the preservation of this rare and ecologically significant species.